Usborne illustrated english dictionary - Bingham, Jane; Brooks, Felicity (Usborne Place of publication not identified, 2014)
Usborne Illustrated English Dictionary is a vibrant and comprehensive reference book that combines clear definitions with engaging illustrations to make learning English fun and accessible.